Mito e argumento no Fédon - Rubens Garcia Nunes Sobrinho (2004)
The present rescareh aims at elarifying the reasons why Plato makes sueh an extensive use of mythieal narratives in his argument, a use whieh is typical of the way his middle period dialogues operate philosophically. In the ilistoiy of Philosophy, Plato's myths have been neglected by scholars who take them to be pieces of "imaginative literature", not worthy of philosophical interest in themselves. On the whole, they are not considered representative of Plato's thought. Nevertheless, the dialectic movement of the Phaccio shows that the use of mythical narratives is not only fundamental to the degree of intelligibility aimed at by philosophical exam, but also a resource which goes beyond the boundaries and demands of strict rational argument. In the first chapter, the point is to establish the operational scope of the philosophical myth in the Phuedo, as opposed to conceptual argument. This is done both by making a clear opposition between myth and concept as well as by establishing an intimate relationship that determines not only the rationality peculiar to myth but also the affection present in dialectical argument. 'fhe second chapter explains the arguments brought forward in favor of the immortality of the soul and the way the imbrication between myth and argument essentially integrates and contributes to the exam of immortality, of knowledge and of philosophical activity itself, 'fhe third chapter develops the dialogue's most important notions and theses, such as the hypothesis of Forms, causality and the issue of an inquiry method that reconciles argument and philosophical myth. The fourth and last chapter is both a detailed interpretation of the fmal eschatological myth and an attempt at establishing a clear relation between the principles of interpretation used and the global argument of the dialogue, 'fhe purpose is to show that the exegesis and the detailed exam of the philosophical myths contribute in a unique way to a deeper understanding of Plato's dialogues. From that perspective, the text opposes and relates two distinct approaches, not always compatible: the fixed allegorical interpretation and a more structural one, according to Burkert and Vernant. As a whole, the careful choice of terms is made through the comparison of different translations of the dialogue (M. Dixsaut, P. Vicaire, G. Reale, R. Hackforth), taking into account the fact that the smallest lexical variations have an amplified impact on the interpretation of the different concepts at stake.